Studying the dynamic characteristics of gas-operated guns using Solidworks Motion software - Nguyen, Phu M.; Vo, Bien V.; Dao, Doan V.; Nguyen, Dung V. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This article presents a new approach to determining the dynamic characteristics of the automatic firing system of gas-operated automatic guns. Methods: Based on the real structure of the automatic firing system of gas-operated automatic weapons, a 3D model of the gun is simulated using Solidworks software, and the dynamic characteristics of the automatic firing system are calculated on Solidworks Motion software.Results: The obtained simulation results include displacement and velocity of the breech platform over time; the force exerted by the hammer on the bolt carrier over time; and impact force of the bolt carrier and gun body over time. These results are compared with data obtained from experiments to verify the mathematical model. The cycle of a shot according to test results is 0.0846 s and the firing rate error between theoretical and experimental results is 2.82%.Conclusion: Research content allows users to visually evaluate the working process of all parts of the automatic firing system. The results of this research can be applied to calculations for automatic firing systems of different automatic guns. This is an important scientific basis for improving and upgrading existing automatic weapons and serving the process of designing and manufacturing new types of automatic weapons in the future.
Keywords: dynamics; automatic firing system; automatic weapons; gas-operated weapons; Solidworks Motion